The Aeneid - Virgil.,Ferry, David,Thomas, Richard F. (University of Chicago Press, 2021)
Intro – Contents – Preface – A Note on Meter – A Note on the Translation – Introduction-Richard F. Thomas (2022) – The Aeneid – Book One – Book Two – Book Three – Book Four – Book Five – Book Six – Book Seven – Book Eight – Book Nine – Book Ten – Book Eleven – Book Twelve – Acknowledgments – Glossary of Names.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books